Pharmacokinetics of Paroxetine Tablets in healthy Arabic Subjects - Jaafar Jaber Ibraheem Al-Tamimi (College of Pharmacy / Mustansiriyah University, 2016)
A single oral dose of paroxetine 20 mg tablets (Seroxat®, GlaxoSmithKline, England) were administered to thirty six healthy male adult fasting subjects to study the pharmacokinetics of the drug in Arabic population.             Twenty blood samples were obtained from each subject up to 96 hours after dosing. The concentrations of paroxetine were monitored in plasma to calculate the pharmacokinetic parameters; Cmax, Tmax, AUC0-t,AUC0-¥,Kel& T0.5;applying non-compartmental analysis.             The mean±SD for the abovementioned parameters were; 3.14±2.09 ng/ml, 5.1±1.28 hr, 48.6±45.9 ng.hr/ml, 59.5±42.3 ng.hr/ml, 0.066±0.022 hr-1 and 11.9±5.1 hrs, respectively. The present investigation demonstrated high inter individual variation particularly in the primary pharmacokinetic parameters Cmax (CV=66.5%), AUC0-t (CV=94.5%), and AUC0-¥ (CV=71%). Beside, comparing the results of the current investigation obtained from Arabic population with that published in other studies conducted in other nations indicating that there is clear population variability in the pharmacokinetic of paroxetine.             Therefore, it can be concluded from the present investigation that individualization and therapeutic drug monitoring are suggested for optimal therapy with paroxetine. However, further investigations are recommended to confirm this suggestion by studying the pharmacokinetics of the drug in Arabic patients and after multiple dosing.